Gênero oral debate: proposta didática para desenvolvimento de estratégia linguístico/discursiva no Novo Ensino Médio a partir de um olhar sobre o livro didático "Se liga nas linguagens" - Souza, Maurilio Macedo de (2024)
Within the scope of the renewed High School, the oral debate genre emerges as a key piece in pedagogical development, highlighting argumentation as a linguistic-discursive strategy of undeniable relevance. This reconfigured educational paradigm aims to not only impart knowledge but also cultivate essential skills for academic life and beyond. Given this context, this research's main objective is to defend the relevance of the oral debate genre as a linguisticdiscursive strategy in the context of New High School through the elaboration of a didactic proposal. For specific objectives, analyze how debate contributes to the development of students' oral expression skills; investigate the influence of the oral debate genre in promoting critical thinking and students' ability to argue; Propose a didactic sequence for the practice of the oral debate genre to encourage critical thinking and students' ability to argue. In the final analysis of the research on the oral debate genre in the new High School, it is proposed to explore not only an educational methodology, but a path towards comprehensive training, capable of facing the complex challenges of academia and contemporary society. Therefore, during the study, we addressed the concepts of textual genre in the conception of Marcuschi (2011); gender debate and teaching of the Portuguese Language according to the PCNs and BNCC of the Portuguese Language; and teaching orality based on the concepts of Antunes (2009), Moraes (2021), Dolz, Schneuwly and Haller (2011) and other authors. The main result is that the work in question is aligned with the BNCC, emphasizing the development of skills that go beyond conceptual knowledge, including socio-emotional skills and attitudes. The didactic proposal covers the thematic axes of the BNCC, maintaining language practices from Elementary School, and highlights the importance of promoting skills such as learning to learn and acting with discernment in digital cultures. The analysis suggests specific improvements in the approach to the oral genre "debate", aiming to stimulate deeper discussions and strengthen students' argumentative skills.